2021
DOI: 10.1007/s41348-021-00537-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic variability of fungal isolates associated with the Septoria leaf spot disease of lettuce (Lactuca sativa) in Brazil

Abstract: Septoria leaf spot is a severe disease of lettuce in tropical and subtropical regions, inducing yield/quality losses and increasing production costs. Globally, Septoria lactucae has been reported as the major pathogen associated with this disease. However, a complex of Septoria species has been also reported in association with lettuce crop around the world. Extensive surveys of Septoria species associated with this disease have not been conducted in the Neotropics. Therefore, the objective of the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Sep13 (063.482 TRA), Sep26 (063.490 TRA), Sep34 (063.496 TRA) and Sep39 (063.501 TRA). All these isolates were classi ed as S. lactucae via molecular analyses (Cabral et al, 2022). The isolates were cultivated in 9 cm diameter Petri dishes containing oatmeal and agar culture medium (60 grams of oat our + 18 grams of agar + 1000 mL of distilled water) in an incubator type BOD at constant temperature of 17 o C (12 hours light and 12 hours dark) for 13 days until sporulation (Dhingra and Sinclair 1995) for each isolate.…”
Section: Screening Germplasm Accessions From Distinct Lettuce Morphot...mentioning
confidence: 99%
See 2 more Smart Citations
“…Sep13 (063.482 TRA), Sep26 (063.490 TRA), Sep34 (063.496 TRA) and Sep39 (063.501 TRA). All these isolates were classi ed as S. lactucae via molecular analyses (Cabral et al, 2022). The isolates were cultivated in 9 cm diameter Petri dishes containing oatmeal and agar culture medium (60 grams of oat our + 18 grams of agar + 1000 mL of distilled water) in an incubator type BOD at constant temperature of 17 o C (12 hours light and 12 hours dark) for 13 days until sporulation (Dhingra and Sinclair 1995) for each isolate.…”
Section: Screening Germplasm Accessions From Distinct Lettuce Morphot...mentioning
confidence: 99%
“…During each of these stages, multiple diseases can affect the development of lettuce plants. Septoria leaf spot has been a very common disease in the vegetative phase in lettuce-producing regions with mild temperatures (20-24°C) and in places with rainy weather or sprinkler-irrigation systems (Blancard et al, 2006;Cabral et al, 2022). The disease is more severe in the transition from the vegetative to the reproductive stage, and can often affect stems and oral organs in seed production elds (Bedlan, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During each of these stages, multiple diseases can affect the development of lettuce plants. Septoria leaf spot has been a very common disease in the vegetative phase in lettuce-producing regions with mild temperatures (20-24°C) and in places with rainy weather or sprinkler-irrigation systems (Blancard et al, 2006;Cabral et al, 2022). The disease is more severe in the transition from the vegetative to the reproductive stage, and can often affect stems and oral organs in seed production elds (Bedlan, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although Septoria leaf spot of lettuce has been reported to be induced by a complex of fungal species of the genus Septoria in other continents (Bedlan, 1999;Lohmeier et al, 2013), recent molecular characterization of a wide range of isolates indicated Septoria lactucae Passerini (family Mycosphaerellaceae) as the sole causal agent of this disease under Brazilian conditions (Cabral et al, 2022). The identi cation and incorporation of resistance/tolerance factors to S. lactucae into commercial cultivars is a central strategy for Septoria leaf spot management as well as other seed-borne pathogens (Cabral et al, 2019).…”
Section: Introductionmentioning
confidence: 99%